The analysis of evaluation items of CPNS k1/k2 pre-service training participants group III DKI Jakarta Province 2018 - Yanto Suharto (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2019)
The analysis of evaluation items is performed to determine the quality of the final evaluation instrument for pre-service training participants. This research is conducted using the Anates version 4.00 application with quantitative approaches and descriptive methods. The subjects of the study are CPNS K1/K2 Group III pre-service training participants of DKI Province, class 131-132 in 2018 as many as 60 people with 50 items of multiple choice evaluation items. The results of the analysis show that out of 50 items, there are 26 valid questions based on the correlation coefficient of 0.354 at the 1% significance level, and the correlation coefficient of 0.273 at the 5% significance level. Based on the results of the overall recap, 26 questions (52%) can be used. Those consist of questions 18 items (36%) that can be directly used and 8 items (16%) questions that can be used but must be corrected, while those that cannot be used or dropped are 24 items (48%).